2023
DOI: 10.1186/s12955-023-02096-z
|View full text |Cite
|
Sign up to set email alerts
|

A head-to-head comparison of the EQ-5D-5L and 15D descriptive systems and index values in a general population sample

Abstract: Background The EQ-5D-5L and 15D are generic preference-accompanied health status measures with similar dimensions. In this study, we aim to compare the measurement properties of the EQ-5D-5L and 15D descriptive systems and index values in a general population sample. Methods In August 2021, an online cross-sectional survey was conducted in a representative adult general population sample (n = 1887). The EQ-5D-5L and 15D descriptive systems and inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Further, the brevity and ease of administration of the EQ-5D-3L, which uses 3-level Likert scales, delivers a practical advantage with respect to its burden on respondents compared with other instruments with more dimensions. Nevertheless, it must be considered that the EQ-5D-3L has a higher ceiling effect than other generic instruments, such as the SF-36, SF-6D [ 111 , 112 ], 15D [ 136 ], and NHP, with the 15D and SF-6D showing the lowest effect [ 137 , 138 ]. However, it should be noted that the EQ-5D-5L, which consists of a 5-level Likert scale used in three studies [ 54 , 82 , 97 ], has been shown to reduce this ceiling effect [ 139 , 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the brevity and ease of administration of the EQ-5D-3L, which uses 3-level Likert scales, delivers a practical advantage with respect to its burden on respondents compared with other instruments with more dimensions. Nevertheless, it must be considered that the EQ-5D-3L has a higher ceiling effect than other generic instruments, such as the SF-36, SF-6D [ 111 , 112 ], 15D [ 136 ], and NHP, with the 15D and SF-6D showing the lowest effect [ 137 , 138 ]. However, it should be noted that the EQ-5D-5L, which consists of a 5-level Likert scale used in three studies [ 54 , 82 , 97 ], has been shown to reduce this ceiling effect [ 139 , 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, presenting population norms for multiple questionnaires from a common sample is rare [ 35 37 ], making it a unique opportunity for a comprehensive comparison. Although the Hungarian versions of EQ-5D-5L, PROPr and SF-6D showed good validity [ 26 , 27 , 38 47 ], their population norms have not yet been developed. This study therefore primarily aims to develop general population reference values for the EQ-5D-5L, PROPr and SF-6D based on a large sample of the adult general population in Hungary.…”
Section: Introductionmentioning
confidence: 99%